From seismic interpretation to modelling and assessment of oil and gas fields - Ampilov, Yury P. (EAGE Publications, 2010)
In this publication the author pays special attention to the cross-disciplinary problems of the geosciences: seismic processing and interpretation, geological and hydrodynamic modelling and he analyses the contradictions of the applied methods. The author states that narrow specialization in geosciences has hindered unbiased subsurface investigation. There is a need for new specialists who are able to integrate knowledge from the different fields. The book provides critical but unbiased analysis of the interpretation possibilities of seismic exploration when forecasting rock properties. Moreover, compared to the Russian version, this edition gives a more extended analysis of seismic inversion algorithms. This book will be useful for geologists, geophysicists, engineers involved in the development of hydrocarbon fields and other, cross-disciplinary specialists. --